2013
DOI: 10.3389/fpsyg.2013.00566
|View full text |Cite
|
Sign up to set email alerts
|

Music and speech prosody: a common rhythm

Abstract: Disorders of music and speech perception, known as amusia and aphasia, have traditionally been regarded as dissociated deficits based on studies of brain damaged patients. This has been taken as evidence that music and speech are perceived by largely separate and independent networks in the brain. However, recent studies of congenital amusia have broadened this view by showing that the deficit is associated with problems in perceiving speech prosody, especially intonation and emotional prosody. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 115 publications
9
70
1
Order By: Relevance
“…Ciocca et al, 2002;Green et al, 2004;Laneau et al, 2004). The fi ndings of better F0 discrimination in the CIm group in turn echo the fi ndings in NH listeners participating in musical training (Micheyl et al, 2006;Hausen et al, 2013). Duration discrimination varied only slightly between groups, and, as in other The pattern of results for forward digit span broadly showed the same effects of hearing status and music experience as seen with F0 discrimination, with the CIn group performing less well than the NH and CIm group, although the latter difference was signifi cant only at the 2nd measurement point, while the CIm group performed equivalently to the NH group.…”
Section: Accuracy and Development Of Auditory Discrimination: Effectssupporting
confidence: 57%
See 2 more Smart Citations
“…Ciocca et al, 2002;Green et al, 2004;Laneau et al, 2004). The fi ndings of better F0 discrimination in the CIm group in turn echo the fi ndings in NH listeners participating in musical training (Micheyl et al, 2006;Hausen et al, 2013). Duration discrimination varied only slightly between groups, and, as in other The pattern of results for forward digit span broadly showed the same effects of hearing status and music experience as seen with F0 discrimination, with the CIn group performing less well than the NH and CIm group, although the latter difference was signifi cant only at the 2nd measurement point, while the CIm group performed equivalently to the NH group.…”
Section: Accuracy and Development Of Auditory Discrimination: Effectssupporting
confidence: 57%
“…KISsankello " or " KISsan KELlo " (English translation " BLUebell " or " BLUe BEll " ) (Vogel & Raimy, 2002;O ' Halpin, 2010;Hausen et al, 2013). Responses were made by pointing at a picture representing the object.…”
Section: Perception Of Word and Sentence Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal musical training studies consistently suggest that music training provides speech-related benefits, such as phonological awareness, perception of vowel duration, and speech segmentation, to NH listeners (Hausen, et al, 2013; Degé & Schwarzer, 2011) and benefits in melodic and pitch perception to CI users (Chen et al, 2010; Galvin, et al, 2007). Torppa et al (2014) found that CI children participating in music or dance activities over a period of 16 months performed similarly to NH children in tasks of pitch discrimination and word stress perception, whereas CI children participating in non-musical tasks over the course of the study performed more poorly.…”
Section: Review Of Prosody and Voice Emotion Studies In Cochlear Imentioning
confidence: 99%
“…This interpretation assumes some degree of domain-general rhythm, in which musical rhythm and speech prosody use shared cognitive resources 74,75 and individual differences in domain-rhythm skills account for language outcomes. The literature to date has not yet differentiated whether shared mechanisms for rhythm and grammar connections are bolstered also by underlying differences in auditory working memory 76 or hierarchical processing, 57 as suggested by our findings of an association between music rhythm skills and complex syntax.…”
Section: Conclusion: Mechanisms For Shared Rhythm and Grammar And Futmentioning
confidence: 99%